2021
DOI: 10.1525/collabra.29766
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Associations Between Parenting and Child Big Five Personality Traits

Abstract: The goal of this research was to explore the relationships between four parenting dimensions (academic involvement, structure, cultural stimulation, and goals) and child personality development. Many theories, such as social learning, attachment theory, and the psychological resources principle assume that parenting practices influence child personality development. Most of past research on the associations between parenting and child Big Five traits specifically has used cross-sectional data. The few longitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 79 publications
0
1
0
Order By: Relevance
“…It has been shown that low socioeconomic status and living in a socioeconomically deprived neighborhood are both associated with more frequent experiences of loneliness and social isolation 32 . Offspring temperament may also be among the potential mediators in the intergenerational transmission of social interaction patterns and relationship qualities, given that parenting is known to predict the temperament and personality of offspring 33 35 . The most prominent temperament characteristic that may affect loneliness is sociability, referring to the degree to which a child is comfortable with and approaches new people and new situations as opposed to being shy, withdrawn or reserved 36 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that low socioeconomic status and living in a socioeconomically deprived neighborhood are both associated with more frequent experiences of loneliness and social isolation 32 . Offspring temperament may also be among the potential mediators in the intergenerational transmission of social interaction patterns and relationship qualities, given that parenting is known to predict the temperament and personality of offspring 33 35 . The most prominent temperament characteristic that may affect loneliness is sociability, referring to the degree to which a child is comfortable with and approaches new people and new situations as opposed to being shy, withdrawn or reserved 36 .…”
Section: Introductionmentioning
confidence: 99%